2022
DOI: 10.14202/vetworld.2022.647-654
|View full text |Cite
|
Sign up to set email alerts
|

Study of fecal glucocorticoid metabolites in captive Asian elephants in Kanchanaburi Province, Thailand

Abstract: Background and Aim: Over the past two decades, the number of elephant camps in Thailand has increased considerably, and captive elephants have become more popular within the tourism industry. Tourist activities involving elephant exhibitions and trekking potentially affect animal health and welfare. This study aimed to investigate the relationships between a novel stress biomarker, fecal glucocorticoid metabolites (fGCM), and various factors (sex, age, weather season, tourist season, and elephant usage pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In 2016, a series of epidemiological studies of elephants in North American zoos revealed problems associated with ovarian acyclicity ( 45 ), health and musculoskeletal function ( 46 ), stereotypic behaviors ( 35 ), and high body condition scores ( 47 ). A similar set of studies on tourist elephants in Thailand found similar problems associated with elevated stress hormones ( 48 ), excessive body condition and metabolic derangements ( 49 ), and stereotypies ( 50 ). Finally, surveys of thousands of elephants in hundreds of tourist venues across Thailand, India, Nepal, Sri Lanka, Laos, Cambodia, and Malaysia suggest that more than half (63%) are kept in inadequate conditions ( 51–53 ).…”
Section: Introductionmentioning
confidence: 82%
“…In 2016, a series of epidemiological studies of elephants in North American zoos revealed problems associated with ovarian acyclicity ( 45 ), health and musculoskeletal function ( 46 ), stereotypic behaviors ( 35 ), and high body condition scores ( 47 ). A similar set of studies on tourist elephants in Thailand found similar problems associated with elevated stress hormones ( 48 ), excessive body condition and metabolic derangements ( 49 ), and stereotypies ( 50 ). Finally, surveys of thousands of elephants in hundreds of tourist venues across Thailand, India, Nepal, Sri Lanka, Laos, Cambodia, and Malaysia suggest that more than half (63%) are kept in inadequate conditions ( 51–53 ).…”
Section: Introductionmentioning
confidence: 82%